Correction: Estremera-Pedriza et al. Optical Characterization of a New Facility for Materials Testing under Concentrated Wavelength-Filtered Solar Radiation Fluxes. Solar 2023, 3, 76–86 - Noelia Estremera-Pedriza; Jesús Fernández-Reche; Jose A. Carballo (Solar)
Following publication, the Editorial Office became aware that the original article [...]